2011
DOI: 10.1149/1.3572272
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Electronic Properties of MOS Interface in Nanoscale MOSFETs

Abstract: Fluctuations in the number, energy level, and carrier capture rate of Si/SiO 2 interface traps in small-gate-area metal-oxidesemiconductor field-effect transistors (MOSFETs) containing only a few interface traps have been directly observed. This observation is based on an understanding of charge pumping phenomena and a newly observed phenomenon of on(off)-time-dependent charge pumping characteristics in their rising (falling) portion. It is directly shown from experimental results that the fluctuation in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The charge pumping (CP) technique (1,2) is known to be the only highly-precise method for evaluating the density of interface traps even in extremely small-area MOSFETs, and many studies on the in-depth exploration of traps near the MOS interface have been reported using the CP method (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). This method will become a more powerful technique for investigating the interface traps in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The charge pumping (CP) technique (1,2) is known to be the only highly-precise method for evaluating the density of interface traps even in extremely small-area MOSFETs, and many studies on the in-depth exploration of traps near the MOS interface have been reported using the CP method (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). This method will become a more powerful technique for investigating the interface traps in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The charge pumping (CP) technique 2,3) is known to be the only highly-precise method for evaluating the density of interface traps even in extremely small-area MOSFETs, and many studies on the in-depth exploration of traps near the MOS interface have been reported using the CP method. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] This method will become a more powerful technique for investigating the interface traps in the future. In the CP method, a pulsed voltage is applied to the gate to alternately form inversion and accumulation layers under a constant reverse-biased source/drain-junction.…”
Section: Introductionmentioning
confidence: 99%